Integrasi Kurikulum Kewirausahaan dalam Pendidikan Pesantren Sebagai Upaya Mencetak Santripreneur - Qistin toniyah Zamrud (TSAQAFATUNA : Jurnal Ilmu Pendidikan Islam, 2025)
This study examines the integration of the entrepreneurship curriculum at Pondok Darul Hijrah Buntet Pesantren Cirebon as an effort to produce santripreneurs*, driven by the need to transform pesantren into centers for student economic empowerment. Using a qualitative case study approach, data were collected through observation, interviews, documentation, and questionnaires involving leaders, teachers, business unit managers, and 60 final-year students, and analyzed using the Miles and Huberman model. The findings indicate both intracurricular integration through entrepreneurship subjects and extracurricular integration through practical business activities; 82% of students reported improved practical skills, and 65% expressed interest in starting a business after graduation—indicating the program’s effectiveness in fostering motivation and entrepreneurial readiness. These results affirm that the entrepreneurship curriculum effectively shapes santripreneurs and can serve as a sustainable model for Islamic-based economic education.